Pengembangan Model Latihan Speed, Agility, Quickness (SAQ) Untuk Meningkatkan Kelincahan Atlet Tenis Yunior - syati, gita laras; Nasuka, Nasuka (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research is to develop a SAQ (Speed, Agility,Quickness ) training model, analyzing the effect of developing a training model to increase agility . This research uses the R&D (research and development ) method. The quantitative data analysis technique in this research uses descriptive statistics using a Likert scale . , Analysis of Variance (Anova) at the significant level (0.005). The population in this study was the Pantai Timur Tennis Club (10 Athletes) for small group trials and the Volta Tennis Club (22 Athletes) for large group trials. The results of the research show that: the results of the field tennis validator with a percentage of 81% description